Adapted Nakazima test to evaluate dynamic effect on strain distribution and dome height in balanced biaxial stretching condition. (November 2018) - Sasso, M.; Mancini, E.; Chiappini, G.; Simoncini, M.; Forcellese, A.
Highlights: The study has been focused of the effect of high strain rates on sheet formability in balanced biaxial stretching condition. An experimental equipment, based on the Nakazima test standard, has been designed and then mounted on a direct Hopkinson bar. Dynamic tensile tests on AA6082 sheet samples have been carried out using the same direct Hopkinson bar. The strain distribution over the dumbbell-like and Nakazima specimens has been evaluated by means of optical methods. The tested alloy exhibits a relevant increment in the strain to failure when passing from quasi-static to high rate of loading. Abstract: The knowledge of formability is important for the success of sheet metal forming processes. Notwithstanding they can involve relatively high speeds, higher than the quasi-static regime ones, few studies considering the strain rate effect on formability are available in literature. In the present paper, a study on the effect of strain rate on formability of AA6082 aluminum alloy, with a thickness of 1 mm, has been carried out. In order to evaluate the formability under dynamic loading conditions an experimental equipment, based on the Nakazima test, mounted on a direct tension-compression split Hopkinson bar (SHB), has been designed. The standard SHB method was also used to perform tensile to study the high strain rate behavior of AA6082 sheets. The results have been compared with the ones obtained in quasi-static conditions and engineering and true stress and strain data have been collected. A fast camera has been used to acquire images of the sheet samples during tests to obtain the true strain distribution. The study has been focused of the effect of high strain rates on sheet formability in balanced biaxial stretching condition. Graphical abstract: